Efforts to Increase Pesticide Label-Reading - Rodolfo N. Salcedo; Hadley Read; James F. Evans; Ana C. Kong (Journal of Applied Communications, 1973)
Four years of work with the Pesticides Regulation Division of the U. S. Environmental Protection Agency have given us a unique opportunity to learn something about pesticide labels and the dynamics of their use.